2021
DOI: 10.1177/20503121211054988
|View full text |Cite
|
Sign up to set email alerts
|

Central obesity and its predictors among adults in Nekemte town, West Ethiopia

Abstract: Background: Abdominal obesity is emerging as a major contributor to the worsening of non-communicable diseases. There is a dearth of data on central obesity among adults in Ethiopia in general and in the study area in particular. The aim of this research was to determine the prevalence of central obesity and its predictors among adults in Nekemte, Ethiopia. Methods: Community-based cross-sectional study was conducted in Nekemte town from March to April 2020. Multistage sampling technique was used to select 466… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 31 publications
10
17
1
Order By: Relevance
“…In this study, women had 13 times higher odds of central obesity compared to men. This finding is corroborated by similar studies in different parts of Ethiopia (35-39). Similarly, studies conducted by Jaacks et al ., suggested that in countries with stage 1 obesity transition, the prevalence of obesity is higher among women compared to men (45).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, women had 13 times higher odds of central obesity compared to men. This finding is corroborated by similar studies in different parts of Ethiopia (35-39). Similarly, studies conducted by Jaacks et al ., suggested that in countries with stage 1 obesity transition, the prevalence of obesity is higher among women compared to men (45).…”
Section: Discussionsupporting
confidence: 88%
“…In comparison to men, women had a higher prevalence of central obesity (53.1% vs 15.4%). The figures reported in this study are comparable with studies conducted in Gondar and Dabat towns, Northwest Ethiopia (37.6% & 33.6%) (37,43), but higher than the studies conducted in Nekemte town, West Ethiopia (28.4%) (35), Woldia town, Northeast Ethiopia (15.5%) (36), and Dilla town South Ethiopia (24.4%) (38). The possible variations of the obesity prevalence could be explained by the use of different cutoff values for waist circumferences (36) and the variation of age distributions between the studies participants (35,38).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with the findings of the study done in Ethiopia (Nekemte town), South Africa, Uganda, and Tanzania. 20 , 21 , 47 , 48 This is due to the hormonal changes at the time of menopause, and fat that is regained after the postpartum period relatively, which is stored more in the central part of the body; additionally, the cultural way of comforting women after giving birth, especially in Ethiopia, are the reasons that will cause women to be the centrally obesity population. The other possible reason for this variation in prevalence could be that females have more steroid hormones which expose them to obesity; 42 the use of hormonal contraceptives are other possible factors.…”
Section: Discussionmentioning
confidence: 99%